2007
DOI: 10.1161/01.atv.0000259357.42089.dc
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl Ester Transfer Protein (CETP) Expression Protects Against Diet Induced Atherosclerosis in SR-BI Deficient Mice

Abstract: Objective— To determine whether expression of the human CETP transgene protects against diet-induced atherosclerosis in SR-BI deficient mice. Methods and Results— SR-BI deficient (−/−) mice were crossed with CETP transgenic (CETPtg) mice to produce a colony of SR-BI −/− × CETPtg mice in a C57Bl/6 background. Age and sex matched groups of genetically modified and wild-type C57Bl/6 mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…In the human situation, an improper functioning of CLA-1 is expected to be compensated for by the presence of CETP, a protein that redistributes cholesteryl esters from HDL to ApoB-containing lipoproteins, including LDL, leading to an alternative uptake route of cholesteryl esters by the adrenals. In our experiments, we confirm that expression of human CETP in SR-BI KO mice indeed leads to the transfer of cholesteryl esters from the relatively large HDL particles to ApoB-containing lipoproteins accessible for LDL receptormediated internalization (32). As already anticipated, the presence of CETP in SR-BI KO mice resulted in an increased delivery of cholesteryl esters from HDL via ApoB-containing lipoproteins to the adrenals.…”
Section: Resultssupporting
confidence: 88%
“…In the human situation, an improper functioning of CLA-1 is expected to be compensated for by the presence of CETP, a protein that redistributes cholesteryl esters from HDL to ApoB-containing lipoproteins, including LDL, leading to an alternative uptake route of cholesteryl esters by the adrenals. In our experiments, we confirm that expression of human CETP in SR-BI KO mice indeed leads to the transfer of cholesteryl esters from the relatively large HDL particles to ApoB-containing lipoproteins accessible for LDL receptormediated internalization (32). As already anticipated, the presence of CETP in SR-BI KO mice resulted in an increased delivery of cholesteryl esters from HDL via ApoB-containing lipoproteins to the adrenals.…”
Section: Resultssupporting
confidence: 88%
“…expression diminishes plasma total cholesterol levels and has a major impact on HDL cholesterol content and particle size in SR-BI Ϫ/Ϫ mice (23,24). Under chow diet feeding, we also observed that SR-BI Ϫ/Ϫ /CETP mice exhibited a 1.5-fold decrease in plasma TC as compared with non-CETP transgenic animals ( Table 1).…”
Section: Impact Of Cetp Expression On Plasma Cholesterol Levels and Hsupporting
confidence: 57%
“…These data are consistent with the recent observation that CETP expression attenuated the development of atherosclerosis in SR-BI-KO mice. 18 These data could also have direct relevance to human physiology. Schwartz and colleagues have demonstrated that in humans the vast majority of HDL CEs that are ultimately secreted into bile are transported to the liver by apoB-containing lipoproteins.…”
Section: Discussionmentioning
confidence: 95%